Host response of Arabidopsis thaliana ecotypes is determined by Sclerotinia sclerotiorum isolate type - Ge, Cynthia; Barbetti, M. (Springer Netherlands, 2018)
© 2018, Koninklijke Nederlandse Planteziektenkundige Vereniging. Studies were undertaken to characterise the interactions of eight Sclerotinia sclerotiorum isolates/pathotypes on leaves of intact plants of 17 Arabidopsis thaliana ecotypes. For lesion diameter and lesion incidence, there were significant (P = 0.001) effects of pathogen isolates, A. thaliana ecotypes, and a significant interaction between isolates and ecotypes in all three experiments. Resistance to S. sclerotiorum infection across the ecotypes ranged from highly susceptible through to resistant and the bioassay was sensitive enough to allow assessment of small differences in partial relative resistances across the ecotypes. While some A. thaliana ecotypes, such as Sha, Bay-0, Ws-1 and Ws-2, were found to be highly susceptible to all S. sclerotiorum isolates tested, others, such as Er-0, Jea and Cvi-0, showed a consistent level of resistance, and of these latter, Er-0 showed the highest and most consistent expression of resistance. In contrast, Col-0, Nd-0 and Oy-0 responses ranged from relative resistant to highly susceptible, depending upon the isolate being tested. Some isolates, such as MBRS1, elicited a wide range of resistance responses across the ecotypes, making these isolates most useful for screening the full range of A. thaliana ecotypes for their responses to S. sclerotiorum. In contrast, other isolates such as ‘Cabbage’ only generated lesions over a very narrow size range of host resistance response and hence could limit the ability of such isolates to differentiate resistances across diverse A. thaliana populations. Increasing the number of ecotypes tested increased the capacity to differentiate both the levels of relative resistance amongst test ecotypes and the varying levels of aggressiveness between different isolates. This is the first known study to demonstrate how Arabidopsis resistance responses can be expressed or compromised by variation in aggressiveness amongst different S. sclerotiorum isolates and/or pathotypes.